Primary care quality and its effects on leprosy monitoring indicators - Nayara Figueiredo Vieira; José Ramón Martínez-Riera; Francisco Carlos Félix Lana
ABSTRACT Objectives: to evaluate the quality of primary care in leprosy control actions, to correlate effects on monitoring indicators. Methods: a cross-sectional study, conducted in Belo Horizonte, from July to September 2014. Interviews with 408 professionals were conducted through the application of a tool that assesses attributes of primary care in leprosy control actions, and monitoring indicators were calculated. Spearman correlation was used, significance level p < 0.05. Results: the overall score correlated with the percentage of cases treated in primary care and of family health staff coverage. The derived score correlated with the percentage of cases treated in primary care, and the essential score correlated with the proportion and rate of cases diagnosed, with grade 2 physical disability. Conclusions: the quality of leprosy control actions performed by primary care professionals produces impacts on health indicators, and developing strategies consistent with the reality of the territory is necessary.